2013
DOI: 10.1016/j.transproceed.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative, Randomized Trial of Concentration-Controlled Sirolimus Combined With Reduced-Dose Tacrolimus or Standard-Dose Tacrolimus in Renal Allograft Recipients

Abstract: Background. The clinical safety and efficacy of sirolimus plus reduced-dose tacrolimus was evaluated in de novo renal allograft recipients enrolled in a comparative, open-label study. Methods. One hundred twenty-eight renal allograft recipients were randomly assigned (1:1) to receive reduced-dose tacrolimus plus sirolimus (rTAC) or standard-dose tacrolimus and sirolimus (sTAC) for 6 months. The primary efficacy endpoint was calculated creatinine clearance values at 6 months. Results. Demographic variables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The most widely reported strategy identified by our literature search was CNI minimization, implemented by reducing target trough levels. Thirty‐six RCTs (Table S4) examining dose minimization were identified: 22 studies used CsA, 7 used tacrolimus and 7 incorporated both. Mycophenolic acid formulations (mycophenolate mofetil [MMF] or enteric‐coated mycophenolate sodium [MPS]) were used as adjuvant agents in 19 studies, and 14 used mammalian target of rapamycin (mTOR) inhibitors in addition to CNI.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely reported strategy identified by our literature search was CNI minimization, implemented by reducing target trough levels. Thirty‐six RCTs (Table S4) examining dose minimization were identified: 22 studies used CsA, 7 used tacrolimus and 7 incorporated both. Mycophenolic acid formulations (mycophenolate mofetil [MMF] or enteric‐coated mycophenolate sodium [MPS]) were used as adjuvant agents in 19 studies, and 14 used mammalian target of rapamycin (mTOR) inhibitors in addition to CNI.…”
Section: Resultsmentioning
confidence: 99%
“…Rapamycin is also known as another denomination sirolimus [69] and is used in combination with the calcineurin inhibitor tacrolimus as maintenance immunosuppressants in transplantation to selectively block the transcriptional activation of cytokines [43, 70, 71]. Importantly, Rapamycin binds two proteins, the FK506- (tacrolimus-) binding protein (FKBP) and FKBP-Rapamycin-associated protein (FRAP, the primal nomination of MTOR), in regulating cellular signaling [72, 73].…”
Section: Resultsmentioning
confidence: 99%
“…Tacrolimus is a potent immunosuppressant, and several animal experiments and clinical applications have demonstrated that it has a similar immunosuppressive effect to cyclosporin A (Cys A), with more potent immunosuppressive effects, compared with CysA (10-100-fold higher) and fewer side effects (25). Previous studies have found that tacrolimus not only forms a basis for immunosuppression to prevent kidney transplant rejection, but also for the treatment of chronic allograft nephropathy and lupus nephritis, which can significantly delay glomerulosclerosis and tubulointerstitial damage (26,27). Studies have shown that tacrolimus inhibits transforming growth factor-β-induced kidney tubular epithelial cell transdifferentiation, which may be an important mechanism of tacrolimus in treating organ rejection post-transplantation, and which also provides a theoretical basis for the prevention and treatment of renal fibrosis (28).…”
Section: Discussionmentioning
confidence: 99%